A novel deletion variant in TRAPPC2 causes spondyloepiphyseal dysplasia tarda in a five-generation Chinese family - Cai Zhang; Caiqi Du; Juan Ye; Feng Ye; Renfa Wang; Xiaoping Luo; Yan Liang (BMC, 2020)
Abstract Background Spondyloepiphyseal dysplasia tarda (SEDT) is a rare X-linked recessive inherited osteochondrodysplasia caused by mutations in the TRAPPC2 gene. It is clinically characterized by disproportionate short stature and early onset of degenerative osteoarthritis. Clinical diagnosis can be challenging due to the late-onset of the disease and lack of systemic metabolic abnomalites. Genetic diagnosis is critical in both early diagnosis and management of the disease. Here we reported a five-generation Chinese SEDT family and described the novel molecular findings. Methods Detailed family history and clinical data were collected. Genomic DNA was extracted from venous blood samples of family members. The exons of genes known to be associated with skeletal disorders were captured and deep sequenced. Variants were annotated by ANNOVAR and associated with multiple databases. Putative variants were confirmed by Sanger sequencing. The identified variant was classified according to the American College of Medical Genetics (ACMG) criteria. Results The proband was a 27-year-old Chinese male who presented with short-trunk short stature and joint pain. His radiographs showed platyspondyly with posterior humping, narrow hip-joint surfaces, and pelvic osteosclerosis. A pedigree analysis of 5 generations with 6 affected males revealed an X-linked recessive mode of inheritance. Affected males were diagnosed as SEDT according to the clinical and radiological features. Next-generation sequencing identified a novel variant of c.216_217del in the exon 4 of TRAPPC2 gene in the proband and other affected males. This variant resulted in the shift of reading frame and early termination of protein translation (p.S73Gfs*15). The mother and maternal female relatives of the proband were heterozygous carriers of the same variant, while no variations were detected in this gene of his father and other unaffected males. Based on the ACMG criteria, the novel c.216_217del variant of the TRAPPC2 gene was the pathogenic variant of this SEDT family. Conclusion In this study we identified the novel pathogenic variant of of c.216_217del in the gene of TRAPPC2 in this five-generation Chinese SEDT family. Our findings expand the clinical and molecular spectrum of SEDT and helps the genetic diagnosis of SEDT patients.